2016
DOI: 10.1007/s40259-016-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Analytical Similarity of Proposed Amgen Biosimilar ABP 501 to Adalimumab

Abstract: BackgroundABP 501 is being developed as a biosimilar to adalimumab. Comprehensive comparative analytical characterization studies have been conducted and completed.ObjectiveThe objective of this study was to assess analytical similarity between ABP 501 and two adalimumab reference products (RPs), licensed by the United States Food and Drug Administration (adalimumab [US]) and authorized by the European Union (adalimumab [EU]), using state-of-the-art analytical methods.MethodsComprehensive analytical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 26 publications
1
63
0
2
Order By: Relevance
“…Comprehensive analytical assessment of ABP 501 compared with adalimumab has shown that the two molecules are highly similar in physicochemical properties and biological activity . Additionally, a phase I single‐dose study conducted in healthy adults has demonstrated pharmacokinetic equivalence of ABP 501 to adalimumab .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Comprehensive analytical assessment of ABP 501 compared with adalimumab has shown that the two molecules are highly similar in physicochemical properties and biological activity . Additionally, a phase I single‐dose study conducted in healthy adults has demonstrated pharmacokinetic equivalence of ABP 501 to adalimumab .…”
Section: Discussionmentioning
confidence: 54%
“…TNF‐α) important in the immunopathogenesis of moderate‐to‐severe psoriasis, are safe and effective . Analytical and functional evaluations have demonstrated that ABP 501 and adalimumab are highly similar in their structural and functional properties, as well as biological activity . A phase I, single‐dose study of ABP 501 in healthy adults demonstrated similar pharmacokinetics to that of adalimumab .…”
mentioning
confidence: 99%
“…Currently, the “goalpost” for analytical similarity is defined by the historical performance of the originator’s process and process changes/improvements via characterization of multiple commercial drug product lots to form an analytical target profile (ATP) 22,23,30,32 . The RM 8671 ATP is that of a single homogenized batch.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP may include analytical characterization (e.g., primary structure, size variants, charge variants, glycosylation and other PTMs), biophysical characterization (HOS, colloidal stability, conformational stability), as well as biological characterization (e.g., in vitro binding studies, potency assays) 22,23 . The subset of analytical measurements we used to characterize the non-originator materials in this study demonstrated moderate differences.…”
Section: Discussionmentioning
confidence: 99%
“…Trp side chain cleavage), which was subsequently confirmed to proceed under exposure to ambient light . Forced degradation (including thermal forced degradation) has also become an important tool for biosimilar analysis . However, certain limitations of forced degradation studies of proteins must also be acknowledged.…”
Section: Introductionmentioning
confidence: 99%